Os impactos das medidas dos acordos Brasil - FMI no crescimento e desenvolvimento da economia brasileira (1990-2001) - Macedo, Alexandre Ferreira (2003)
In the present dissertation, we search for impacts of macroeconomic adjustment programs agreed between Brazil and IMF during the period 1990-2001. After a short review about Brazilian externaI debt, we discuss the secrecy in Fund operations. At the same time, we verif)r if Brazil performs the goals of the agreement. At last, we analyze the impacts making use of the classical model of national accounts. Having in mind that no exist documents relating to the period 1990-2001 available for the public, the building of time series remains damaged. Thus, this analysis is empírical, elaborated from data of IMF and Brazilian government.